Go Green Products Using Ecoprint Techniques - Sulaiman, Eman; Budiastuti, Endah; Pratiwi, Vina Andita; Herlina, Ellin; Suwandi; Virgiyanti; Kosasih, Asep (Research and Social Study Institute, 2022)
The purpose of this community service (PKM) is to help increase the economic value of the community from the sale of Batik Ecoprint, improve public knowledge by processing and to utilize natural resources, and produce environmentally friendly products (go green). This method is in the form of training to make batik works by using natural materials such as leaves that are around residential residents with the subject in Plumbon District, Cirebon Regency with the following stages: 1). Preparation stage. 2). Implementation stage The implementation of the training. 3). Lecture and simulation methods (direct practice). 4). Evaluation stage As an indicator of the success of community service. Implementation The results of the implementation of making motifs using the eco print technique show that: a) Activities can be carried out according to plan, b) Materials that have been planned can be carried out well, c) The results of the work of activity participants become personal property and tote bags can be used in dily activities and even sold d) The success of the activity participants in the skills of making eco print technique motifs with the guidance of mentors and the enthusiasm of the participants from the community element.